2001
DOI: 10.1161/hc5001.100833
|View full text |Cite
|
Sign up to set email alerts
|

Activation Delay After Premature Stimulation in Chronically Diseased Human Myocardium Relates to the Architecture of Interstitial Fibrosis

Abstract: Background-Progressive activation delay starting at long coupling intervals of premature stimuli has been shown to correlate with sudden cardiac death in patients with hypertrophic cardiomyopathy. The purpose of this study was to elucidate the mechanism of increased activation delay in chronically diseased myocardium. Methods and Results-High-resolution unipolar mapping (105, 208, or 247 recording sites with interelectrode distances of 0.8, 0.5, or 0.3 mm, respectively) of epicardial electrical activity was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
248
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(266 citation statements)
references
References 29 publications
16
248
0
2
Order By: Relevance
“…27 Kawara et al reported the correlation of conduction delay with a fibrotic tissue pattern in chronic diseased myocardium, including HCM, particularly in areas of patchy fibrosis. 28 In this study, QRS duration on standard 12-lead ECG was associated with lethal arrhythmic events only in the univariate analysis (Table 3); however, the severity of fibrosis in the tissue samples was weakly associated with a longer delayed potential (LAS40) (Figure S2). These findings suggest that the increased fibrosis in HCM associated with longer QRS duration and positive LP represented by prolonged delayed potential detected by SAECG indicates an abnormal conduction delay and may contribute at least in part to the increased incidence of lethal ventricular arrhythmias or SCD.…”
Section: Discussionmentioning
confidence: 64%
“…27 Kawara et al reported the correlation of conduction delay with a fibrotic tissue pattern in chronic diseased myocardium, including HCM, particularly in areas of patchy fibrosis. 28 In this study, QRS duration on standard 12-lead ECG was associated with lethal arrhythmic events only in the univariate analysis (Table 3); however, the severity of fibrosis in the tissue samples was weakly associated with a longer delayed potential (LAS40) (Figure S2). These findings suggest that the increased fibrosis in HCM associated with longer QRS duration and positive LP represented by prolonged delayed potential detected by SAECG indicates an abnormal conduction delay and may contribute at least in part to the increased incidence of lethal ventricular arrhythmias or SCD.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that excessive connective tissue and fibroblasts can act as a current sink for connected CMs, obstruct electrical excitation, and contribute to discontinuous conduction and arrhythmia (11,18,34). Similarly, a recent study also reported that cocultures of CMs and myofibroblasts disrupted electrical coupling and field potential propagation between CMs (36).…”
Section: Discussionmentioning
confidence: 92%
“…It is reasonable to expect that cellular, structural morphological, and parallel electrophysiological changes in the atrial tissue play a more prominent role in the progressive enlargement and hypertrophy of the atria. [10,11] Restoration of sinus rhythm by ablation leads to a greater quality of life (QoL), especially when compared with patients who have persistent AF that experience a sustained abnormal heartbeat and undergo mitral valve surgery. [12] Moreover, Pappone et al [13] reported reduced mortality and morbidity and an improved QoL in patients who underwent circumferential pulmonary vein ablation for AF versus those treated with medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%